Adult Respiratory Syncytial Virus Infection and Hypoxic Cardiac Arrest—Coexistent or Causal? A Hypothesis-Generating Case Report - Sebastian Schnaubelt; Felix Eibensteiner; Marieke Merrelaar; Daniel Tihanyi; Robert Strassl; Christian Clodi; Hans Domanovits; Heidrun Losert; Michael Holzer (Medicina, 2022)
Respiratory syncytial virus (RSV) is a well-known pathogen in paediatric patients. However, it also causes substantial morbidity and mortality in adults, posing a major healthcare problem. We present a patient with chronic pulmonary conditions and an acute RSV infection, thus leading to cardiac arrest (CA). We speculate that RSV as the causative agent for CA should be considered in post-resuscitation care. From a wider public health perspective, immuno-naivety for RSV caused by the coronavirus disease 2019 pandemic may induce a severe rise in cases, morbidity, and mortality in the future.